PELATIHAN MENGGUNAKAN BAHASA INGGRIS UNTUK ANAK SD - M. Ndraha, Lies Dian (Universitas Nias Raya, 2022)
The purpose of this service is to provide basic English training which is carried out in Hilisataro Village. The method of implementing this service is in the form of lectures and speaking exercises with teenagers in Hilisataro village. The result of this dedication is that many students from elementary and junior high levels are able to speak English, as well as English pronunciation which is almost mastered by children in Hilisataro Village.